Assessment of the Usefulness of the SEMA5A Concentration Profile Changes as a Molecular Marker in Endometrial Cancer - Dziobek, Konrad; Opławski, Marcin; Grabarek, Beniamin O.; Zmarzły, Nikola; Kieszkowski, Przemysław; Januszyk, Piotr; Kiełbasiński, Kamil; Kiełbasiński, Robert; Boroń, Dariusz (Current Pharmaceutical Biotechnology, 2020)
Background: Semaphorin 5A (SEMA5A) functions not only in the nervous system but also in cancer transformation where its role has not yet been sufficiently studied and described. Objective: The aim of the study was to determine the changes in SEMA5A expression in endometrial cancer at various degrees of its differentiation (G1-G3) compared to control. Materials and Methods: The study group consisted of 45 patients with endometrial cancer at various grades: G1, 17; G2, 15; G3, 13. The control consisted of 15 women without neoplastic changes in the routine gynecological examination. The statistical analysis of immunohistochemical assessment of SEMA5A level was carried out using the Statistica 12 program based on the Kruskal-Wallis test and Dunn’s post-hoc test (p<0.05). Results: The expression of SEMA5A (optical density) was observed in the control group (Me = 103.43) and in the study group (G1, Me = 140.72; G2, Me = 150.88; G3, Me = 173.77). Differences in expression between each grade and control and between individual grades turned out to be statistically significant (p<0.01). The protein level of SEMA5A expression increased with the decreasing degree of endometrial cancer differentiation. Conclusion: In our research, we indicated the overexpression of SEMA5A protein in endometrial cancer. It is a valuable starting point for further consideration of the role of SEMA5A as a new supplementary molecular marker in endometrial cancer.
Keywords: endometrial cancer